1982
DOI: 10.1104/pp.69.4.804
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Cadmium Binding Complexes of Cabbage and Tobacco

Abstract: Cadmium complexes with apparent molecular weights of 10,000 were observed in aqueous extracts of Cd-treated cabbage (Brassica capitata L., cv. red danish) and tobacco (hybrid of Ncotana glauca and N. langsde,ffii) plants. The amount of complex (as Cd) recovered was found to be dependent on the concentration of the metal in the growth medium and the total time of exposure of plants to the metal. Induction of the complex at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

1984
1984
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 14 publications
0
28
0
2
Order By: Relevance
“…The above data and a very high degree of specificity in the response of plants to particulate metals (8) suggest that proteins play a role in tolerance mechanisms. These mechanisms can function in two ways: either the metal is metabolized into stable metaloproteins, like cadmium in cabbage (Brassica oleracea L.) (24) or it is complexed. In the latter case, proteins can serve as specific carriers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above data and a very high degree of specificity in the response of plants to particulate metals (8) suggest that proteins play a role in tolerance mechanisms. These mechanisms can function in two ways: either the metal is metabolized into stable metaloproteins, like cadmium in cabbage (Brassica oleracea L.) (24) or it is complexed. In the latter case, proteins can serve as specific carriers.…”
Section: Methodsmentioning
confidence: 99%
“…The modified 'pulse' method was used for screening varieties and hybrid populations of wheat (2). The Al concentration in nutrient solution that caused irreversible damage of root apical meristem in 4-d-old seedlings during 24 were added at concentrations of 2.5 uCi/ml (4 ,ug/ml) and 10 ,uCi/ml (10 The distribution of Al in root subcellular fractions from induced and control Atlas 66 seedlings was studied using the methods described earlier (20). Significantly more Al was found in all fractions from pretreated roots than in controls (Table IV), but the relative distribution of Al between subcellular fractions was unchanged.…”
Section: Methodsmentioning
confidence: 99%
“…Weigel and Jager (1980) demonstrated that Cd in Phaseolus vulgaris seedlings was mainly bound to peptides and low molecular weight proteins. ln cabbage and tobacco leaves an inducible Cd binding protein of Me 10,000 was reported by Wagner and Trotter (1982), similarly almost all of the Cd in aqueous extracts of lycopersicon esculentum was recovered in association with an inducible protein fraction of Me 10,000 (Bartolf et al, 1980). Rauser (1984) isolated an inducible Cd binding polypeptide from Agrostis gigantea which contained over 90% of the ;oluble Cd.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was not until 1980 that the existence of metal binding proteins was first reported in higher plants (Rauser and Curvetto, 1980). Subsequently, they have been found to occur in a number of plant species; for example, tomato (Lue-Kim and Rauser, 1986), soybean (Cataldo et al, 1981), wheat (Wagner and Nulty, 1984), tobacco and ~abbagc (Wagner and Trotter, 1982;Wagner and Yeargan, 1986). Grill et al (1985) isolated a group of Cd binding polypeptides from cell suspension cultures of more than a dozen different plant species and referred to these as phytochclatins.…”
Section: Introductionmentioning
confidence: 99%
“…Rechromatography of fraction B (Fig. 1) plants can be classified as a type of metallothionein which differs from that in animals (3)(4)(5)(6)(7)(8)(9). Characterization of this material in detail is in progress.…”
Section: Introductionmentioning
confidence: 99%